11 Junior doctors as senior leaders – lessons learnt during COVID-19. (16th November 2020) - Home, Joseph
Abstract : COVID-19 presented a huge unplanned pressure on health resources worldwide. Across the NHS, different approaches have been utilised to respond to the crisis. Leadership figures across services were faced with difficult decisions with potential scarcity of resources never before seen by NHS services, particularly in relation to critical-care bed capacity. One of the key changes implemented in the acute Trust where I am based, was the placement of a junior doctor into Trust management and Leadership teams. Under direct supervision from the Trust director team I was released from the majority of my clinical responsibilities to provide leadership and oversight into decisions affecting junior doctors. This included leading junior doctor redeployment, inducting Foundation Induction Year 1 Doctors and designing and implementing a new out-of-hours service. As a FY2 doctor, this provided a unique experience to integrate into senior management structures and and lead several projects. Coming from a baseline of poor trainee feedback across several cohorts, it was recognised that this was an opportunity to instigate a culture shift across divisions. This article will discuss the lessons learnt from this experience, highlighting areas for improvement, with the hope of providing a road-map for empowering junior doctors to take senior leadership roles in the future.